Addressing Key Clinical Care and Clinical Research Needs in Severe Pediatric Traumatic Brain Injury: Perspectives From a Focused International Conference - Nacoti, Mirco; Fazzi, Francesco; Biroli, Francesco; Zangari, Rosalia; Barbui, Tiziano; Kochanek, Patrick M., The Collaborative Pediatric TBI Working Group; Bertolini, Guido; Bonanomi, Ezio; Bressan, Silvia; Chiara, Osvaldo; Citerio, Giuseppe; et al. (Frontiers in Pediatrics, 2021)
Traumatic brain injury (TBI) is a leading cause of morbidity and mortality in children and adolescents. Survivors of severe TBI are more prone to functional deficits, resulting in poorer school performance, poor health-related quality of life (HRQoL), and increased risk of mental health problems. Critical gaps in knowledge of pathophysiological differences between children and adults concerning TBI outcomes, the paucity of pediatric trials and prognostic models and the uncertain extrapolation of adult data to pediatrics pose significant challenges and demand global efforts. Here, we explore the clinical and research unmet needs focusing on severe pediatric TBI to identify best practices in pathways of care and optimize both inpatient and outpatient management of children following TBI.